The Role of Experiential Value in Mediating the Effect of Product Quality and Service Encounter on Customer Loyalty at Tomoro Coffee Balikpapan - Firlianzo, Muhammad; Kuleh, Yohanes; Adhimursandi, Doddy (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study investigates the mediating role of experiential value in the relationship between product quality, service encounter, and customer loyalty at Tomoro Coffee Balikpapan. The research aims to understand how customers’ perceived experiences influence their loyalty in the modern coffee shop industry. Using a quantitative approach which is data were collected through questionnaires distributed to 162 respondents who are regular customers of Tomoro Coffee. The data were analyzed using PLS-SEM with SmartPLS 4.0 software. The results show that product quality and service encounter have a positive and significant effect on experiential value and customer loyalty. Furthermore, experiential value has a positive and significant impact on customer loyalty and acts as a partial mediator in the relationship between product quality, service encounter, and customer loyalty. These findings confirm that customer experiences play a crucial role in transforming perceptions of quality and service into long-term loyalty. The study contributes theoretically by reinforcing the importance of experiential marketing and value creation in the coffee shop industry, while practically guiding managers to enhance both tangible and intangible service aspects to strengthen customer loyalty